PERSEPSI PETANI TERHADAP TEKNOLOGI “PANCA KELOLA” DI LAHAN RAWA BEKAS TERBAKAR (Kasus lahan gambut bekas terbakar Desa Talio Hulu Kecamatan Pandih Batu Kab. Pulang Pisau) - Yanti Rina Darsani; Yiyi Sulaeman; Masganti Masganti (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
To understand the potential for increasing rice production on burnt peatlands, a demo farm (demonstration of grouped farming and fishing) which is a collaboration between Balittra and BRG which covers an area of 38 ha in Talio Hulu Village, Pandih Batu District, Pulang Pisau Regency, Central Kalimantan in 2020-2021. This study aims to discover the farmers' perceptions of the technology components and performance of rice cultivation technology. The activities have been carried out on farmers' land by applying “Five Management” technology include (1) water management techniques; (2) land preparation, (3) amelioration and fertilization (4) utilization of new high yielding varieties with high yield potential, and (5) integrated pest and disease control. Data were collected from 24 cooperating farmers by survey method. Primary data were collected by conducting direct interviews with farmers using a structured questionnaire. The data collected was tabulated and analyzed descriptively. The results showed that burned peatlands have the potential to increase rice production. The results showed that burned peatlands have the potential to increase rice production.. The response of farmers to the components of rice cultivation technology is positive. The five technology components that have the highest value with a value of 95.83% are (1) water regulation in paddy fields, (2) the utilization of ash and urea fertilizer in the nursery, (3) the utilization of manure and lime as ameliorant, (4) the utilization of urea fertilizer, SP-36, and NPK, and (5) the utilization of natural phosphate. The farmer's perception of the Five Management technology is positive.  Economically, rice farming of the Inpara 2 variety is efficient (R/C = 1.14).